Analisis Penurunan Kadar Glukosa Darah Mencit (Mus musculus) Jantan yang Diberi Ekstrak Metanol Daun Cemba (Acacia pennata) Asal Enrekang Diinduksi Aloksan - Maulana, Aji; Suryani, Irma; A. Mu’nisa, A. Mu’nisa (Fakultas MIPA UNM, 2017)
Abstract. The Plants Cemba (Acacia pennata) included in family Leguminoceae, which is typical plant in Enrekang, South Sulawesi. The purpose of this research is to determine the effect of methanol extract of cemba leaves to decrease blood glucose levels in mices male ICR strain induced by alloxan. The leaves were extracted using 96% methanol by maceration method. This study is a randomized complete design (RAL), which contains of 5 treatments and 5 replicates. The extract was dissolved using Carboxy Methyl Cellulose (CMC) 0.5% and given orally in mices that had been previously injected by alloxan 120 mg/kg intraperitoneally. The awarding of the extract given different doses i.e., 125, 250 and 500 mg/kg. The data were Analyzed using Analysis of Variance (ANOVA) using SPSS 2.0 Program and continued by Duncan test (α 0:05), as drugs control using glibenclamide 5 mg / kg whereas the normal control using CMC 0.5%. The results showed that 250 mg/kg dose of the extract had a most effective to decrease blood glucose levels during 14 days of given cemba leaves extract. These results were significantly different with negatif control (105.6 mg/dl) and positif control (105.80 mg/dl), as well as groups of mice that were given the cemba leaves extract 150 and 500 mg/kg. Extract of cemba leaves shows the effect of the decrease blood glucose levels in mices male.Keywords: cemba leaves extract, family Leguminoceae, Enrekang.